TRANSFORMASI OTONOMI DESA: PUDARNYA KEKUASAAN FORMAL DESA DALAM PENYELENGGARAAN PEMERINTAHAN PADA MASA ORDE BARU (KASUS DESA NEGLASARI KECAMATAN SALAWU KABUPATEN TASIKMALAYA) - Iyep Saefulrahman; Utang Suwaryo (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2016)
AbstractAutonomy for the village as the law community unit is a power to regulate and manageits own people’s interest that can be transformed based on different of state perspective. Afundamental transformation in the degree of power that belongs to village, it occurred in thevillage in the governing of the new order. It is also experienced by Neglasari, Salawu SubRegency, Tasikmalaya Regency. This study aimed to analyze the autonomy of transformationthat occurred in Neglasari governance in the New Order. Indirectly, this paper also aimsto explain the existence of institutional power locally, at the same time state strengthen itsposition in the village through village autonomy transformation policy. With the aim of suchresearch, the method used is qualitative research and data collection techniques using in-depthinterviews and documentation. In Neglasari, the transformation of village autonomy impacton power dissipation of the village which is indicated by changes in the organization structureand its governance. Transformation also have an impact on power of decision-making and theelection of its leader. Babadamian as a holding that powers changes from formal to be informalbecause its power because their roles and functions taked out by village institutional wichtformed by state. Nevertheless, its changed doesn’t imfluence of babadamian exixtence becausebabadamian still has power to village government and villagers.Kata kunci: Transformasi, Otonomi Desa, dan Penyelenggaraan Pemeintahan.